Relationship between Socio-Emotional Competencies and the Overlap of Bullying and Cyberbullying Behaviors in Primary School Students - Juan Manuel Rodríguez-Álvarez; Santiago Yubero; Raúl Navarro; Elisa Larrañaga (MDPI AG, 2021)
Digital life forms part of daily reality for young people. For this reason, traditional bullying in school has been reproduced in the online environment, resulting in an overlap of off- and online bullying. Research on socio-emotional competencies and bullying is revealing interesting results among students in secondary schools. However, studies involving primary school students are much scarcer. In addition, the majority of studies have been carried out based on an understanding of socio-emotional competencies as a unidimensional construct. In the present study, we examined the overlap between off- and online bullying victimization and the influence of the factors comprising socio-emotional competencies on this overlap. Participants comprised 1130 students (49.7% were boys and 50.3% were girls) from the fifth and sixth grades at 15 schools in the autonomous communities of Madrid and Castilla-La Mancha (Spain). The results indicate a high rate of overlap between off- and online bullying victimization, without significant gender differences. Poor relationship skills in boys and low self-management in girls were associated with being a victim of both traditional bullying and cyberbullying. The conclusions point to an interesting line of intervention and prevention, establishing a framework of confluence for social and emotional variables within the primary education context.